The Unintended Consequences of Social Media in Healthcare: New Problems and New Solutions - Hors-Fraile, S.; Atique, S.; Mayer, M. A.; Denecke, K.; Merolli, M.; Househ, M. (Yearbook of Medical Informatics, 2016)
Objectives: Social media is increasingly being used in conjunction with health information technology (health IT). The objective of this paper is to identify some of the undesirable outcomes that arise from this integration and to suggest solutions to these problems.Methodology: After a discussion with experts to elicit the topics that should be included in the survey, we performed a narrative review based on recent literature and interviewed multidisciplinary experts from different areas. In each case, we identified and analyzed the unintended effects of social media in health IT.Results: Each analyzed topic provided a different set of unintended consequences. Most relevant consequences include lack of privacy with ethical and legal issues, patient confusion in disease management, poor information accuracy in crowdsourcing, unclear responsibilities, misleading and biased information in the prevention and detection of epidemics, and demotivation in gamified health solutions with social components.Conclusions: Using social media in healthcare offers several benefits, but it is not exempt of potential problems, and not all of these problems have clear solutions. We recommend careful design of digital systems in order to minimize patient’s feelings of demotivation and frustration and we recommend following specific guidelines that should be created by all stakeholders in the healthcare ecosystem.
Keywords: Social media; gamification; epidemics; chronic disease; outcomes; ethics; legal; crowdsourcing